(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Work performance refers to the outcome or behaviour exhibited by extension agents (EA) to perform certain job activities over a specific period. Using Transfer of Technology (ToT) and Human Resources Development (HRD) competencies, the work performance (WP) of EAs was assessed. This research aimed to determine which skills, contribute the most towards WP of EAs perceived by productive cocoa farmers (PCF) in Malaysia and determine the most performed EA between areas. This study derived from the Iceberg Model of competencies and employed quantitative methods with a well-structured questionnaire. A sample of 353 and 315 PCFs, for the Peninsular and East Malaysia, respectively, who have attended two training programs exposed by EA and have cultivated cocoa for five to seven years. The respondents were chosen through a multi-stage sampling method. Descriptive and multiple regression analyses were used. The results revealed that social, leadership, technical, and decision-making support skills from Peninsular Malaysia have significantly contributed to the WP. Social skill is the factor that contributes the most to the WP of EA in Peninsular Malaysia. For East Malaysia, only three skills, namely, decision-making support, technical, and leadership skills contributed to WP significantly. Decision-making support skill is the highest contributing skill to WP of EA in East Malaysia. Then, the EA in Peninsular Malaysia performed better than Eastern Malaysia because the R2 value for Peninsular Malaysia is greater than the of Eastern Malaysia, which is 0.637 and 0.521, respectively. In conclusion, MCB agency may focus on relevant skills by area to improve the WP of their EA.